Use of the knowledge to action model improved physical therapist adherence to a common clinical practice guideline across multiple settings: a multisite case series - Julie K. Tilson; Clarisa A. Martinez; Sara MacDowell; Linda J. D'Silva; Robbin Howard; Heidi R. Roth; Karen M. Skop; Elizabeth Dannenbaum; Lisa Farrell (BMC, 2022)
Abstract Background When a new guideline is published  there is a need to understand how its recommendations can best be implemented in real-world practice. Yet, guidelines are often published with little to no roadmap for organizations to follow to promote adherence to their recommendations. The purpose of this study was to evaluate the impact of using a common process model to implement a single clinical practice guideline across multiple physical therapy clinical settings. Methods Five organizationally distinct sites with physical therapy services for patients with peripheral vestibular hypofunction participated. The Knowledge to Action model served as the foundation for implementation of a newly published guideline. Site leaders conducted preliminary gap surveys and face-to-face meetings to guide physical therapist stakeholders' identification of target-behaviors for improved guideline adherence. A 6-month multimodal implementation intervention included local opinion leaders, audit and feedback, fatigue-resistant reminders, and communities of practice. Therapist adherence to target-behaviors for the 6 months before and after the intervention was the primary outcome for behavior change. Results Therapist participants at all sites indicated readiness for change and commitment to the project. Four sites with more experienced therapists selected similar target behaviors while the fifth, with more inexperienced therapists, identified different goals. Adherence to target behaviors was mixed. Among four sites with similar target behaviors, three had multiple areas of statistically significantly improved adherence and one site had limited improvement. Success was most common with behaviors related to documentation and offering patients low technology resources to support home exercise. A fifth site showed a trend toward improved therapist self-efficacy and therapist behavior change in one provider location. Conclusions The Knowledge to Action model provided a common process model for sites with diverse structures and needs to implement a guideline in practice. Multimodal, active interventions, with a focus on auditing adherence to therapist-selected target behaviors, feedback in collaborative monthly meetings, fatigue-resistant reminders, and developing communities of practice was associated with long-term improvement in adherence. Local rather than external opinion leaders, therapist availability for community building meetings, and rate of provider turnover likely impacted success in this model. Trial registration This study does not report the results of a health care intervention on human participants.